Microorganisms’ Effects and Mechanisms in Ocular Infections: A Systematic Review - Verma, Shivendra; Singh, Shalini (Journal for Research in Applied Sciences and Biotechnology, 2022)
In the world, microorganisms are the main cause of eye illnesses. Common bacterial infections of the eye, if untreated, can damage the eye's structures and lead to blindness and other visual impairments. The eye may get infected from the outside or as a result of bloodstream-borne germs invading the eye. Infectious bacteria can cause eye infections. Blepharitis, conjunctivitis, Listeriosis, keratitis, dacryocystitis, etc. are some of the frequent eye illnesses brought on by bacterial and fungal pathogens. The information on the variety of ocular surface microorganisms has been significantly increased by the series of genome-based methods through 16S rRNA gene-based identification. According to this research, a sufficient number of bacteria have a substantial part in the pathophysiology of eye illnesses, even though certain bacteria contribute to normal ocular processes. As a result, those with good vision can shed light on the intricacy of the ocular microflora and learn more about some visual requirements in addition to their vital contribution to the regular operation of the eye. Under these conditions, it is crucial to establish a quick, dependable, and affordable procedure that will eventually become a standard diagnostic process. In this literature review, many databases have searched, and the review has been methodically conducted to produce specific results for the hard eye infection disorders.